Effects of Compression Tights on Recovery Parameters after Exercise Induced Muscle Damage: A Randomized Controlled Crossover Study. (8th January 2019) - Hettchen, Michael; Glöckler, Katharina; von Stengel, Simon; Piechele, Andrea; Lötzerich, Helmut; Kohl, Matthias; Kemmler, Wolfgang
Abstract : Introduction . Recent meta-analyses on compression garments have reported faster recovery of muscle function particularly after intense eccentric power or resistance exercise. However, due to the complex interaction between cohorts included, exercises involved and compression applied, recovery length and modalities, and outcome parameters selected, only limited practical recommendations can be drawn from these studies. Thus, our aim was to determine the effect of compression tights on recovery from high mechanical and metabolic stress monitored over a longer recovery period. Material and Methods . Using a crossover design, 19 resistance-trained4 t h /5 t h Division German handball players (31.3±7.7 years; 24.1±3.8 kg/m 2 ) were randomly assigned at the start of the project to the compression tight (recovery-pro-tights, cep, Bayreuth, Germany) or the control group. Immediately after a combined lower extremity resistance training and electromyostimulation, participants had to wear compression tights. Compression was applied initially for 24 h and then 12 h intermitted by 12 h of nonuse for a total of 96 h. Primary study endpoint was maximum isokinetic hip/leg-extensor strength (MIES) as determined by a leg-press. Secondary endpoint was lower extremity power as assessed by a counter movement jump. Follow-up assessments were conducted 24, 48, 72, and 96 h postexercise. Outcomes were analyzed using a linear mixed effect model with spherical symmetric within-condition correlation. Results . All 19 participants underwent their allocated treatment and passed through the project strictly according to the study protocol. MIES demonstrated significantly (p=0.003) lower overall reductions (155 N) after wearing compression tights. In parallel, lower extremity power significantly (p<0.001) varies between both conditions with lower reductions in favor of the compression condition. Of importance, full recovery for lower extremity muscle strength or power was still not reached 96 h postexercise. Conclusion . Based on our results we recommend athletes wear compression tights for faster recovery, particularly after intense exercise with a pronounced eccentric aspect.